The effects of GLP-1 agonists on HbA1c and insulin dose among patients with type 1 diabetes - Alhowiti, Amirah; Mirghani, Hyder (Frontiers in Endocrinology, 2025)
Type 1 diabetes mellitus (T1DM) is a common chronic disease, and there is a rising trend globally; insulin is the mainstay therapy. Despite improvements in insulin delivery and monitoring, a significant percentage of patients still fail to reach glycemic targets. There is an increasing interest in using glucagon-like receptor agonists as adjuvant therapy. A high risk of bias limits meta-analysis on the effectiveness of GLP-1 agonists. This meta-analysis aimed to assess the effects of GLP-1 agonists on HbA1c and total daily insulin dose in T1DM. We searched PubMed, Cochrane Library, and Google Scholar for articles investigating the effects of GLP-1 agonists on the HbA1c and total daily insulin dose without limitation to the publication date. The keywords used were GLP-1 agonists, liraglutide, albiglutide, exenatide, glycated hemoglobin, HbA1c, insulin dose, and glycemic control. Out of the 713 articles retrieved, 21 full texts were screened, and 10 trials were included in the meta-analysis. GLP-1 agonists are more effective than placebo in HbA1c reduction, Z = 5.27, SMD, 0.23, 95% confidence interval (CI), 0.14–0.32, with 1.2 mg and 1.8 mg more effective than 0.6 mg, SMD, −0.87, 95% CI, −1.60 to 0.13, and SMD, −0.79, 95% CI, −1.18 to 0.41, respectively. GLP-1 agonists reduce total daily insulin dose SMD, 2.21, 95% CI, 0.43–3.98 with no significant differences between different doses. GLP-1 agonists were effective in HbA1c and total daily insulin reduction among patients with T1DM. Liraglutide 1.2 mg may be more beneficial; further randomized trials focusing on different doses of GLP-1 agonists and hypoglycemia risk are recommended.